Attitude of caregivers, psychiatrists, and nurses toward coercive measures: An observational, survey-based comparative study - Sneha Kulkarni; M. Uma Sankar; Ravi Kumar Dabbiru; Ramsubba Reddy; Sireesha Srinivasa Rao; Minhajzafar Nasirabadi (Telangana Journal of Psychiatry)
Objectives: The primary objective was to compare the attitude of health-care providers (psychiatrists and nursing staff) and caregivers. Materials and Methods: This prospective, survey-based study used the Staff Attitude to Coercion Scale, Morisky Medication Adherence Rating Scale, Oslo Social Support Scale, and the Modified Overt Aggression Scale. Results: Participants (326) included psychiatrists (32.51%), staff nurses (35.58%), and caregivers (31.90%). Health-care professionals scored higher in offense and safety subscale (psychiatrists 3.2 and 5.55; nurses 3.12 and 5.65) compared to caregivers (2.46 and 5.10). In coercion as treatment subscale, caregivers scored least (0.78) (psychiatrists 1.15, nurses 1.92). The difference in these subscales was statistically significant (P = 0.001). There was no significant influence of social support and level of education of caregivers on the use of physical restraint. Of 104 patients, 58.65% were brought with physical restraint. Treatment compliance (n = 85) in stabilized patients was 84.7%. Conclusion: According to health-care providers, the use of coercion was offensive; coercion can be reduced by improving the resources and giving more personal time. All groups acknowledged that coercion infringes on patients’ human rights but supported its use when necessary for ensuring patient care and safety in the environment.